A gentle reminder. Issue 3 (4th November 2014) - M. Watson, Ann
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to address how utilizing positive psychology can be beneficial when academic libraries are faced with obstacles and challenges. Design/methodology/approach – Opinion piece. Findings – Personal observations. Originality/value – Personal opinion and experience.